2020
DOI: 10.1097/pgp.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic and Ovarian Recurrence of Small HPV-associated Cervical Adenocarcinoma With Transformation to Neuroendocrine Carcinoma

Abstract: The phenomenon of small human papillomavirus-associated cervical adenocarcinomas involving the ovary via a transuterine and transtubal route is uncommon but well described in the literature. We report a unique case of a small human papillomavirus-associated cervical adenocarcinoma spreading to both ovaries and the pelvis via this route 22 mo after loop excision and trachelectomy and developing into a high-grade neuroendocrine carcinoma in the metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has been reported that lung adenocarcinoma and bladder adenocarcinoma transdifferentiated to SCLC and SCBC due to treatment pressure [62,63]. In cervical cancer, the development of neuroendocrine carcinoma from small HPV-associated AdCC has recently been reported [64]. Although the mixed adenocarcinoma component is the common pattern in mixed SCCC, the origin of SCCC, whether derived from adenocarcinoma or reserve cells of the cervix, remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lung adenocarcinoma and bladder adenocarcinoma transdifferentiated to SCLC and SCBC due to treatment pressure [62,63]. In cervical cancer, the development of neuroendocrine carcinoma from small HPV-associated AdCC has recently been reported [64]. Although the mixed adenocarcinoma component is the common pattern in mixed SCCC, the origin of SCCC, whether derived from adenocarcinoma or reserve cells of the cervix, remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the lung and prostate, transdifferentiations from an AdC to neuroendocrine tumor occur in response to targeted therapy [ 14 , 15 ]. However, in cervical cancer, the development of a neuroendocrine carcinoma from a small human papillomavirus–associated cervical adenocarcinoma has been reported lately [ 16 ]. Defining the molecular mechanisms of neuroendocrine transformation in cervical cancer remains a question.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian preservation and ovariectomy have always been controversial for early cervical adenocarcinoma patients (9)(10)(11). The main issues are the risk of ovarian metastasis, the poor prognosis of such patients, and the need to preserve ovarian function in young women.…”
Section: Introductionmentioning
confidence: 99%